Auction mechanisms and bidder collusion: Bribes, signals and selection - Aniol Llorente-Saguer; Ro'i Zultan (Queen Mary University of London, School of Economics and Finance, 2014)
The theoretical literature on collusion in auctions suggests that the first-price mechanism can deter the formation of bidding rings. In equilibrium, collusive negotiations are either successful or are avoided altogether, hence such analysis neglects the effects of failed collusion attempts. In such contingencies, information revealed in the negotiation process is likely to affect the bidding behavior in first-price (but not second-price) auctions. We test experimentally a setup in which collusion is possible, but negotiations often break down and information is revealed in an asymmetric way. The existing theoretical analysis of our setup predicts that the first-price mechanism deters collusion. In contrast, we find the same level of collusion in first-price and second-price auctions. Furthermore, failed collusion attempts distort the bidding behavior in the ensuing auction, leading to loss of efficiency and eliminating the revenue dominance typically observed in firstprice auctions.
Keywords: C72; C91; D44; 330; Auctions; Collusion; Bribes; Experiment